Russian Politics in the Balkans and the 1903 Crisis - Rudolfovich Ayrapetov, Oleg (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
After the suppression of the Boxer Rebellion, the situation in the Far East became increasingly dangerous. The contradictions between Russia and Japan in Manchuria and Korea were growing. To activate its policy in the Far East, Saint Petersburg needed a calm rear in Europe and the Balkans. Meanwhile, the situation in Macedonia threatened to put this rear in jeopardy. Russian-Ottoman relations were threatened by the actions of the VMRO activists and acts of terror committed by Albanians against Russian diplomats. Neither Constantinople nor Saint Petersburg wanted further complications. Nevertheless, Russia was forced to organize a naval demonstration and send its Black Sea Fleet Squadron to the European coast of Turkey. That did not lead to further development of the crisis. Faced with the prospect of a common European diplomatic front, which was based on the Russian-Austrian agreement in Mürzsteg, the Ottoman government took a number of measures against the organizers of terror and accepted a reform program in Macedonia, proposed by Russia and Austria-Hungary.
Keywords: Russia’s policy in the Balkans; the situation in Macedonia; the murders of Russian consuls; naval demonstration of the Black Sea Fleet; the Mürzsteg program